Properties of a Class of -Harmonic Functions - Elif Yaşar; Sibel Yalçın (Abstract and Applied Analysis)
A times continuously differentiable complex-valued function in a domain is -harmonic if satisfies the -harmonic equation , where is a positive integer. By using the generalized Salagean differential operator, we introduce a class of -harmonic functions and investigate necessary and sufficient coefficient conditions, distortion bounds, extreme points, and convex combination of the class.